Transport of L-tryptophan in Saccharomyces cerevisiae - Kotyk, A; Dvoráková, M (Folia microbiologica, 1990)
In addition to the general amino acid transport system (GAP) of S. cerevisiae L-tryptophan is transported by another system with approximately 25% capacity of GAP, with a KT of 0.41 +/- 0.08 mmol/L and with a similar specificity as GAP (lower inhibition by Met, Pro, Ser, Thr and 2-aminoisobutyric acid; greater inhibition by Glu and His). The pH optimum of this system is at 5.0-5.5, activation energy above the transition point (20 degrees C) was 20 kJ/mol, below the transition point 55 kJ/mol. The transport by this system was virtually unidirectional, efflux amounting to at most 10% into a tryptophan-free medium. The transport itself was blocked by 2,4-dinitrophenol, antimycin A and uranyl nitrate. The system was synthesized de novo during preincubation with glucose = fructose greater than trehalose greater than ethanol within 30 min, and was degraded with a half-time of 15 min in the absence of further synthesis. The accumulation ratios of L-tryptophan in gap1 mutants were concentration-dependent (200:1 at 1 mumol L-Trp/L, 4:1 at 2.5 mmol L-Trp/L) and decreased with increasing suspension density from 200:1 to 5:1 (for 10 mumol L-Trp/L). The involvement of hydrogen ions in the uptake was clearly demonstrated by the effect of D2O even if it could not be established by either shifts of pHout or membrane depolarization.
Keywords: koncentrace vodíkových iontů; tryptofan; Mutation; Saccharomyces cerevisiae; Anaerobiosis; teplota; Temperature; anaerobióza; Biological Transport, Active; mutace; Citrulline; Tryptophan; Hydrogen-Ion Concentration; aktivní transport; citrulin